Evaluation of ampicillin, vancomycin, and gentamycin antibiotic resistant among lactobacillus isolates / Rozila Alias... [et al.] - Alias, Rozila; Thivyah, Karunageran; Mustakim, Maimunah; Kamal, Siti Nurfatehah; Mohtar, Siti Hasmah; Hassan, Siti Rahayu; Salina, Murni; Ahmad Khairuddin, Siti Amalina; Muhammad Ali, Hasliza; Mohammad Nawawi, Norazah; Lani, Mohd Nizam; Ibrahim, Abdul Latif (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Antibiotic resistance is an ever-increasing in worldwide problem nowadays. It is happened when the exten- sive use of antibiotics which will creates the selective pressure resulting from mutation of normal genes and spreading of a variety of an antimicrobial resistance. Uses of Lactobacillus as probiotics or in starter cultures may serve as hosts of antibiotic resistance genes, which could be transfer or resistance to multiple antibiotics. Therefore, it is important to screen the susceptible or resistance towards antibiotics which will not transferable resistance genes. In the recent study, a total of 37 strains of Lactobacillus species isolated from various milk and dairy products such as goat’s milk, cattle’s milk, human’s milk, homemade yogurt and commercial yogurt were examined for the antibiotic profile using Kirby-Bauer method. The results of this study show that human’s milk has a high number of Lactobacillus isolates resistant to ampicillin (75%), vancomycin (62.5%) and gentamycin (62.5%). Whereas Lactobacillus isolated from cattle’s milk have resistant to ampicillin (42.1%), vancomycin (42.1%) and susceptible to gentamycin (0%). But however, goat’s milk still has lower percentage number of resistant to ampicillin (28.0%), vancomycin (14.3%) and are susceptible to gentamycin (0%). These results indicate that ampicillin and vancomycin resistant seems to be very common among Lactobacillus isolates but gentamycin are still susceptible used. Vancomycin resistant are more concerned because of the emerging problem in hospital and often described as one of the last resorts against the infection caused by multidrug-resistant pathogens. Therefore, lactobacilli as probiot- ics would be more monitoring when applied in food industry and clinical especially for immune compromised patients or during anti-biotherapy. Acquisition and retransfer of resistance genes should be addressed in the new safety aspects of probiotics uses.addressed in the new safety aspects of probiotics uses.